Benefits of physical exercise in the prevention and management of arterial hypertension in older adults (Research, Society and Development, 2025)
The study aimed to identify scientific evidence regarding the benefits of physical exercise in the prevention and management of arterial hypertension in older adults. An integrative literature review was conducted using the Google Scholar and LILACS databases, following the PRISMA protocol. A total of 173 articles were found, of which 12 met the inclusion criteria. The analysis showed that regular physical exercise, particularly aerobic, resistance, and combined training, significantly reduces blood pressure, improves cardiovascular function, increases cardiorespiratory capacity, and enhances the quality of life of older adults. Additionally, exercise may reduce the need for antihypertensive medications and has positive effects on mental health and social interaction. It is concluded that physical exercise is an effective non-pharmacological intervention that supports the prevention and management of systemic arterial hypertension and plays an essential role in promoting health and autonomy in older adults.